Optic Nerve Hypoplasia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
The pathology, clinical features, and disorders associated with optic nerve hypoplasia in children are reviewed from the Tennent Institute of Ophthalmology, Weston Infirmary, Glasgow, Scotland.